ATP-Sensitive Potassium Channel Currents in Eccentrically Hypertrophied Cardiac Myocytes of Volume-Overloaded Rats - Zikiar V. Alvin; Richard M. Millis; Wissam Hajj-Mousssa; Georges E. Haddad (International Journal of Cell Biology)
ATP-sensitive potassium channels (KATP) protect the myocardium from hypertrophy induced by pressure-overloading. In this study, we determined the effects of these channels in volume-overloading. We compared the effects of a KATP agonist and a KATP antagonist on sarcolemmal transmembrane current density (pA/pF) clamped at 20 mV increments of membrane potential from −80 to +40 mV in ventricular cardiac myocytes. The basal outward potassium pA/pF in myocytes of volume-overloaded animals was significantly smaller than that in the myocytes of sham-operated controls. Treatment of the control myocytes with the KATP agonist cromakalim increased pA/pF significantly. This increase was blocked by the KATP antagonist glibenclamide. Treatment of the hypertrophied myocytes from volume-overloaded animals with cromakalim and in the presence and absence of glibenclamide did not change pA/pF significantly. These findings suggest that eccentrically hypertrophied cardiac myocytes from volume-overloading may be unresponsive to specific activation/inactivation of KATP and that dysfunctional KATP may fail to protect the myocardium from left ventricular hypertrophy associated with volume-overloading.